Performance analysis of protective functions of forest plantations of the Lviv railway line (Ukraine) - Bosak, Pavlo; Lukyanchuk, Nelya; Pinder, Volodymyr; Shukel, Igor; Popovych, Vasyl (Ecological Questions, 2023)
To reduce the harmful impact of railway transport on the environment and ensure environmental safety, railway enterprises develop and implement a wide range of environmentally effective measures annually. First, it concerns the protection of the territories adjacent to the railroad tracks from various types of pollution. These forest plantations are created for the protection of the railroad track from adverse climatic factors, as well as for the reduction of the railway's impact on the surrounding territories - to reduce the various types of pollution, and to protect from adverse aerodynamic effects. In order to investigate the protective properties of forest plantations, we presented their detailed characteristics on the section of the Lviv-Sambir railway line. This is the busiest railway line in terms of the number of trains, which connects the eastern industrial regions of Ukraine with the western part of the European Union. It transports the largest volumes of cargo, including hazardous ones. The effect of afforestation on reducing the heavy metals content in the soil of the impact area of the railway was determined experimentally. In all samples, the concentrations of heavy metals in the soil do not exceed the maximum permissible concentration standards: Cu-100, Zn-100, Pb-30, Cd-3.0 mg/kg3. However, there is a decrease in the heavy metals' content with the distance from the track. Differences in ingredient pollution depending on the placement of plantations were established. Thus, the concentration of heavy metals is higher on average from 2.6% to 29.9% in the areas on the windward side compared to the areas on the opposite leeward side. Therefore, forest vegetation intensively retains heavy metals and performs the function of a filter for the natural environment. Research has established a reduction in the parametric impact of railway transport. The level of protective plantings' effect on noise reduction along railway lines was determined. The highest noise levels of electric trains were determined at 95-94 dBA near the track, at a distance of 50-100 m the noise level remained high at 90-82 dBA, and at a distance of 150-200 m the noise ranged from 86 to 65 dBA; the highest noise levels of passenger trains were determined near the track of 92-91 dBA; freight trains ‒ near the track 93-92 dBA. The dependence of the noise level on the structure and condition of the plantations was determined. Thus, it can be stated that the existing forest plantations perform their phytomelioration functions and reduce the negative ingredient and parametric impact of railway transport. In order to protect the territories adjacent to the railway from pollution successfully, it is necessary to monitor transport sections constantly to ensure the sustainable development of the railway industry.